Ectopic Atrial Tachycardia in a 12-Month-Old Girl Treated With Ivabradine and Beta-Blocker, a Case Report - Michel, Holger; Heißenhuber, Frank; Wellmann, Sven; Melter, Michael; Gerling, Stephan (Frontiers in Pediatrics, 2020)
We report on a 12-month-old girl with an ectopic atrial tachycardia successfully treated with the combination of a beta blocking agent and the novel heart rate lowering agent Ivabradine that acts on cardiac pacemaker cells by selectively inhibiting the If current. Initially commenced standard therapy had to be discontinued due to failure or arrhythmia. No side effects attributed to Ivabradine were noticed. In contrast to adults, where Ivabradine is already widely used, studies in the pediatric age group are missing. Due to its mechanism of action Ivabradine is a promising novel agent for the therapy of tachycardia due to increased automaticity. Reports on the use of Ivabradine in young children or infants with ectopic atrial tachycardia are scarce and this report adds the second described case of this distinct group and novel treatment with Ivabradine to the emerging literature.